Perceptions Towards Behavioral Finance Among Investors in Banking Industry: Evidence from Nepal Bank Limited - Amgain, Pushpa Nidhi (Journal of Economics and Management, 2024)
The purpose of this article is to investigate the attitudes that investors in the banking industry have towards behavioural finance for the purpose of gathering evidence from Nepal Bank Limited. In collaboration with Nepal Bank Limited, the purpose of this study is to investigate the implications of behavioural biases on investment decisions in the banking business. In the context of rational investment decision making on the stock market, the investigation of cognitive biases and emotional biases is measured. After careful consideration, the ontological research philosophy that employs interpretivism research philosophy has been chosen. The researcher has been hired with a semi-structured interview with three investors in the banking business with reference to the Nepal Bank Limited. The data analysis has been done qualitatively using theme analysis. This article presents the findings of the interview. All of the codes were arranged into categories, and themes were discovered. According to the findings of the study, the most common types of behavioural biases that investors in the banking business exhibit are cognitive biases and emotional biases. The evidence for this was obtained from Nepal Bank Limited. Both fundamental and technical analysis were utilised to determine how the outcomes of the study influenced the NBL stock market. In doing so, it brought to light arbitrage possibilities that arise from the psychological and behavioural flaws of investors. These biases include representativeness, availability biases, optimism, overconfidence, and herding behaviour. Because of these biases, individual investors in Nepal Bank Limited were impacted in both their opinions and their behaviour. When it comes to the emotional biases, investors are impacted by psychological and mental accounting, ambiguity aversion, and self[1]control when it comes to making investment decisions in the banking business, as evidenced by Nepal Bank Limited (NBL). The focus of this study is on individual investors; however, it is possible that future research paths may concentrate on institutional investors in the banking industry, supported by evidence from Nepal Bank Limited.